PERANCANGAN UI/UX APLIKASI E-AGENDA BERBASIS WEB MENGGUNAKAN FIGMA (STUDI KASUS : CABANG DINAS PENDIDIKAN WILAYAH KABUPATEN BANYUWANGI) - Ananda Amalia Putri; A. Hamdani; Setyo Agung Wahyudi (Jurnal Riset Teknik Komputer, 2025)
The advancement of information technology has encouraged goeverment institutions to shift toward more efficient and digitally documented work systems. One form of innovations that can be implemented is the development of an E-Agenda application as an electronic activity recording and reporting system. This study aims to design a web – based E-Agenda application to support data management and activity monitoring, particularly within the Banyuwangi District Education Branch Office. The system design method used is the prototype method, as it facilitates iterative communication and better accommodates user needs. The stages of this method include requirements gathering, initial design, prototype development, prototype evaluation, refinement, and system implementation. The outcome of this design is a user interface prototype of the E-Agenda application, developed using tools such as figma, with a simple and user – centered display. Evaluation was conducted through user testing within the institution, resulting in a system that is more practical and relevant. By using the prototype approach, the design process becomes more adaptive to user feedback, resulting in a system that is easier to user, more aligned with user needs, and ready for further development